Color Terms in Shan - Kiatyuddhajati, Suchada (Ganesha Journal, 2021)
The objectives of this article were to analyze basic color terms and non-basic color terms based on the concept of Berlin & Kay and to analyze the social and culture of color terms of the Shan. The data were collected from three Shan texts and from interviewing 15 Shan informants in Pai District, Mae Hong Son Province, whose age was 35 years and over. The research results were as follows. There were nine basic color terms in Shan, which contradicted Berlin & Kay’s color evolution theory, because it was the seventh stage of the evolution. For the formation strategies of the basic color terms, the word “See”, or color, was compounded with the basic color terms. There were four formation strategies of the non-basic color terms. The Shan color terms reflected six aspects of their worldviews or thinking systems. They included natural environment, social conditions, lifestyles, relationships with cultural groups, beliefs, and sicknesses.